Laughter after tears: Sitting for American humors in Indonesian sofas (Subtitling Humors of a Tv Serial Friends) - Sukerti, Gusti Nyoman Ayu; Basthomi, Yazid (citeus, 2016)
The study reported in this paper aims to analyze the possible strategies used in the subtitling of the first five episodes (season 1) of Friends to render the episodes’ humorous dialogues. It examines the subtitler’s strategies in preserving both the semantic and humorous genes of laughter intended by the original humor. The analysis takes into account the internal and external structures of humors both in the target and source language. Choosing a subtitling strategy involves a decisionmaking process where the internal and external factors come into play and, therefore, rendering humors in a contextually bound medium, such as subtitling, does not necessarily work in the TL environment in a consistent manner. The inconsistency highlights the fact that humors, even those considered universal, are not digested in the same manner across cultures.